A dívida pública do Estado do Ceará: análise de choques estruturais no período de 2003 a 2013 - Sousa, Maria Elineide Melo de (2016)
SOUSA, Maria Elineide Melo de. A dívida pública do Estado do Ceará: análise de choques estruturais no período de 2003 a 2013. 2015. 45f. Dissertação (mestrado profissional) - Universidade Federal do Ceará, Programa de Pós Graduação em Economia, CAEN, Fortaleza - Ce, 2015. === Submitted by Mônica Correia Aquino (monicacorreiaaquino@gmail.com) on 2016-02-26T20:00:34Z No. of bitstreams: 1 2015_dissert_memsousa.pdf: 425797 bytes, checksum: 59c9e0404c5f2bb01630a2180284b20f (MD5) === Approved for entry into archive by Mônica Correia Aquino(monicacorreiaaquino@gmail.com) on 2016-02-26T20:00:52Z (GMT) No. of bitstreams: 1 2015_dissert_memsousa.pdf: 425797 bytes, checksum: 59c9e0404c5f2bb01630a2180284b20f (MD5) === Made available in DSpace on 2016-02-26T20:00:52Z (GMT). No. of bitstreams: 1 2015_dissert_memsousa.pdf: 425797 bytes, checksum: 59c9e0404c5f2bb01630a2180284b20f (MD5) Previous issue date: 2015 === The main purpose of this thesis is to shed some light on the indebtedness of Ceara and to analyze its development possibilities. We assume that an adequate evaluation of these possibilities should deal with the ratio between consolidated net debt (CND) and current net income (CNI). From this starting point, we verify if there are any structural breaks with respect the public debt. This evaluation comprehends the period which goes from 2003 to 2013. We also analyze the arguments in favor of minimal common requirements on (CND) – (CNI) and its relationship with these structural weakness. One is the fiscal requirement that says that governments consider such a relationship as an important indicator which plays a vital role on their decision makings such as credit operations. In addition, it will be made a comparative analysis bearing the States of Bahia and Pernambuco. To quantify over the ration between (CND) and (CNI), we employ throughout the thesis the methodologies formulated by Perron and Yabu (2009a, 2009b), respectively. The analysis results show that the State of Ceará still continues keeping a suitable strategy toward the maintenance and control of its indebtedness at supportable levels. And the reason is that the ratio between CND – CNI remains at reasonable levels. Also, as a positive outcome, the State is firmly respecting the Fiscal Responsability Act. The simulations show that there were structural breaks in the three states investigated, though before these all states had negative slope in the ratio CND – CNI. In late 2013 Ceara State appeared as the slightest CND – CNI between the three states analyzed, though showing a growing tendency with respect the CND – CNI after 5th quarter of 2009. Even this, the State of Ceará maintains an affirmative and consistent fiscal sustainability, in virtue of this is that its indebtedness is within the limits stipulated by Fiscal Responsibility Act. === Este estudo analisa a evolução do endividamento do Estado do Ceará, tomando como indicador a razão entre a Dívida Consolidada Líquida (DCL) e a Receita Corrente Líquida (RCL), verificando a existência de quebras estruturais da dívida pública, no período de 2003 a 2013, considerando que esta relação constitui-se em um importante indicador por influenciar a tomada de decisão, no tocante a contratação de operações de crédito pelo Governo. Adicionalmente, é realizada uma análise comparativa com os Estados da Bahia e Pernambuco. Para aferir a evolução desta razão, empregam-se as metodologias desenvolvidas por Perron e Yabu (2009a, 2009b). Os resultados da análise demonstraram que o Estado do Ceará vem mantendo o controle de seu endividamento, contribuindo para que a relação DCL/RCL fique em patamares reduzidos. Desta forma, o Estado está cumprindo a meta estabelecida pela LRF. Os resultados do ensaio evidenciam que ocorreram quebras estruturais nos três estados pesquisados. Antes das quebras estruturais, todos os estados apresentavam inclinação negativa na razão DCL/RCL. O Ceará permanece no final de 2013, com a menor razão DCL/RCL entre os três estados analisados, embora apresente uma tendência crescente da razão DCL/RCL após o 5º bimestre de 2009. Mesmo com a tendência de crescimento identificada, o Estado do Ceará vem mantendo uma estratégia adequada e consistente, contribuindo para que o seu endividamento fique dentro dos limites definidos em lei.